Pengaruh Religiusitas dan Consumer Animosity Terhadap Keputusan Boikot dan Purchase Unwillingness Produk Unilever Indonesia pada Konsumen Generasi Z di Kabupaten Pasuruan - Choirotus Sya’diyah Putri; Kholid Murtadho (MES Management Journal, 2025)
This study analyzes the influence of religiosity and consumer animosity on boycott decisions and purchase unwillingness towards Unilever Indonesia products among Generation Z consumers in Pasuruan Regency. The analysis method used is path analysis with a sample of 114 respondents. The results indicate that religiosity and consumer animosity significantly affect both boycott decisions and purchase unwillingness. This suggests that companies need to consider consumer values in their business practices, especially among Generation Z, who have a significant impact on shaping market dynamics.